The Opportunity Cost of Labor and the Returns to Education under Unemployment and Labor Market Segmentation - Pinera, Sebastian; Selowsky, Marcelo (Quarterly Journal of Economics, 1978)
I. Introduction, 469.—II. Segmented urban labor markets and the existence of voluntary unemployment, 472.—III. The employment-unemployment decision-making process, 473.—IV. Deriving the contribution of labor to output, 476.—V. Empirical evaluation, 479.